2006
DOI: 10.1007/s10936-005-9011-6
|View full text |Cite
|
Sign up to set email alerts
|

Planning at the Phonological Level during Sentence Production

Abstract: KEY WORDS: phonological encoding; planning; picture-word interference paradigm; sentence production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
80
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 45 publications
8
80
2
Order By: Relevance
“…This suggests the verb, part of the first PW, was phonologically encoded before articulation. Phonological encoding of the first PW before articulation of sentences is consistent with previous evidence that phonological planning extends at least one PW in advance (Levelt, 1989;Wheeldon and Lahiri, 1997) and/or planning extends to the verb in sentence production (Smith and Wheeldon, 2004;Schnur et al, 2006;Oppermann et al, 2010a).Having replicated previous results showing phonological planning through the first PW and verb in a different set of sentences, the critical question to be addressed is whether in sentence production phonological planning is non-incremental, extending an entire phonological phrase. If phonological planning in sentence production is defined by phonological phrase boundaries then I expect phonological effects to the direct object NP at articulation of the sentence for sentences like, "He opens the gate."…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This suggests the verb, part of the first PW, was phonologically encoded before articulation. Phonological encoding of the first PW before articulation of sentences is consistent with previous evidence that phonological planning extends at least one PW in advance (Levelt, 1989;Wheeldon and Lahiri, 1997) and/or planning extends to the verb in sentence production (Smith and Wheeldon, 2004;Schnur et al, 2006;Oppermann et al, 2010a).Having replicated previous results showing phonological planning through the first PW and verb in a different set of sentences, the critical question to be addressed is whether in sentence production phonological planning is non-incremental, extending an entire phonological phrase. If phonological planning in sentence production is defined by phonological phrase boundaries then I expect phonological effects to the direct object NP at articulation of the sentence for sentences like, "He opens the gate."…”
supporting
confidence: 85%
“…Similarly, Oppermann et al (2010a) found that participants were faster to produce sentences when phonologically related distractors were related to the first PW and PP before the verb, but no effects were found for the object after the verb (e.g., "Die Maus frisst den Käse": [The mOUse] PW/PP [[EAts] PW [the chEEse] PW/PP ; the verb was not tested). Thus, phonological planning encompassed both a PW and PP, and extended up to the verb of the sentence.The non-incremental view of phonological planning suggests that more is planned in advance of articulation, where the unit of planning may be a phonological phrase (Miozzo and Caramazza, 1999;Costa and Caramazza, 2002;Smith and Wheeldon, 2004;Schnur et al, 2006;Damian and Dumay, 2007). In Schnur et al (2006), participants were faster to produce sentences when distractors were phonologically related to the verb (e.g., [The Orange gIrl] PP [wAlks] PW/PP ) showing that planning extended two phonological phrases.…”
mentioning
confidence: 99%
“…(a) a conversational turn is of no fixed length, adapting to the open-ended or generative character of natural language syntax (Sacks, Schegloff, & Jefferson, 1974); (b) the language production system is quite slow, even a single word requiring 600 msec from conception to articulatory output (Indefrey & Levelt, 2004;Levelt, 1989), and multiword utterances considerably longer (see e.g., Schnurr, Costa, & Caramazza, 2006;Jescheniak, Schriefers, & Hantsch, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, diverging results were reported. While some authors claimed that the unit of encoding is limited to one word (Meyer, 1996), others argued that speakers plan the entire message before speaking (Schnur, 2011;Schnur, Costa, & Caramazza, 2006). A different set of studies focussed on which constraints might modulate phonological planning.…”
Section: The Span Of Encoding At the Phonological Levelmentioning
confidence: 99%
“…The results reported by these studies actually show that the planning unit is subject to inter-individual differences (Gillespie & Pearlmutter, 2011;Michel Lange & Laganaro, 2014;Wagner, Jescheniak, & Schriefers, 2010). Nevertheless, many investigations converge on the span of encoding extending over the initial word, at least in adjectival noun-phrases with prenominal adjectives (Costa & Caramazza, 2002;Damian & Dumay, 2007;Dumay, Damian, Stadthagen-Gonzalez, & Perez, 2009;Schnur et al, 2006). At the interface with the phonetic level, some studies reported syllabic length effect in picture naming tasks with longer naming latencies for words of two syllables relative to one (Santiago, MacKay, Palma & Rho, 2000) and frequency effects for both the first and second syllable of a bisyllabic word (Cholin, Dell & Levelt, 2011) which suggests a span of encoding extending the initial syllable.…”
Section: The Span Of Encoding At the Phonological Levelmentioning
confidence: 99%